REKONSTRUKSI PEMIKIRAN FIKIH: Suatu Gagasan Awal Mencairkan Kebekuan Fikih di Indonesia - Mustafa, Muhtadin Dg. (Hunafa: Jurnal Studia Islamika, 2011)
Indonesia is a countryÂ  whose population is majority Muslim. Thus, the aspects of syariâah (Islamic law) should color the religiousity of Indonesian Muslims. However, the syariah is not static, it is Â dinamic as it alwaysÂ  gets in contact with social aspects. In this context, the reactualization and reconstruction of IslamicÂ  jurisprudence should be continually performed. The reactualization of the Islamic jurisprudence related to pragmatic values covering the patterns Â ofÂ  daily life of the Muslims while the reconstruction the Islamic jurisprudence thought more focuses on conceptual intellectuality values. Based on theÂ  relationship ofÂ  the idea ofÂ  reactualization and reconstruction of the Islamic jurisprudence, it can be concluded that the latter is an infrastructure, while the renewal is a means to realize the function ofÂ  syariah (Islamic law) as a social control and social engineering.